2013
DOI: 10.1016/j.eneco.2013.09.022
|View full text |Cite
|
Sign up to set email alerts
|

Energy poverty alleviation and climate change mitigation: Is there a trade off?

Abstract: Energy poverty alleviation has become an important political issue in the most recent years. Several initiatives and policies have been proposed to deal with poor access to modern sources of energy in many developing countries. Given the large number of people lacking basic energy services, an important question is whether providing universal access to modern energy could significantly increase energy demand and associated CO 2 emissions. This paper provides one of the few formal assessments of this problem by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
89
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 174 publications
(90 citation statements)
references
References 16 publications
1
89
0
Order By: Relevance
“…They found that final energy demand per capita will stand at around 10 Gj in 2030. Chakravarty et al (2013) used the IEA's World Energy Outlook (IEA 2014) projections method to assess individual energy consumption by 2030. They found, for Africa, an aggregate final household energy consumption of 9.5 exajoule (EJ) in a business-as-usual (BAU) case in 2030.…”
Section: Introductionmentioning
confidence: 99%
“…They found that final energy demand per capita will stand at around 10 Gj in 2030. Chakravarty et al (2013) used the IEA's World Energy Outlook (IEA 2014) projections method to assess individual energy consumption by 2030. They found, for Africa, an aggregate final household energy consumption of 9.5 exajoule (EJ) in a business-as-usual (BAU) case in 2030.…”
Section: Introductionmentioning
confidence: 99%
“…The final model after all those steps, is written down here as Equation (2). CO2t = β1Ct + β2Rt + β3Ct(-1)+ β4Ct(-2)+ β5CO2t(-1) + et (2) where CO2t represents the CO2 emissions from the electricity sector in the year t, Ct and Rt represent the amount of coal and renewable energies utilization by the electricity sector respectively, Ct(-1) and Ct(-2) are the first and second lags of Ct respectively and CO2t(-1) represents the first lag of CO2t. β1 to β5 are the coefficients of the variables of Equation (2) respectively.…”
Section: Methods and Approachmentioning
confidence: 99%
“…These findings, however, contradict the previous outcomes of other studies. Chakravarty and Tavoni [2] have tried to shed light on energy consumption and its impacts on pollutant emissions mitigation in the horizon of 2030. Using a statistical model, the authors have mapped global energy consumption and have come to the conclusion that meeting the energy poverty eradication policy by 2030, the global temperature would raise by 0.13 °C.…”
Section: Fig 1 Co2 Emitted By the Electricity Sector Vs Renewable mentioning
confidence: 99%
“…The price of oil is the most sensitive to the poor, while climate change affects mostly the livelihood of farmers and fishermen. The need for energy poverty alleviation for the next 20 years should be balanced with reducing 7% energy consumption of individuals, but still, increase 0.13 o C global temperature (Chakravarty & Tavoni, 2013). Related to the live of poor farmers, recent research have been addressed to agriculture and rural development, such as the work of Bellon, et al, (2005) and Farrow, Larrea, Hyman, & Lema(2005).…”
Section: Introductionmentioning
confidence: 99%